IMPROVING LISTENING AND SPEAKING ACHIEVEMENTS OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 6 METRO BY USING VIDEOS PLUS DISCUSSION METHOD - Rizka Amalia (Jurnal Pedagogy, 2016)
Listening and speaking are the important skills that have to be mastered by the students. By having these skills, the students can communicate with others easily. However, the teaching and learning of listening and speaking skills are still problematical. The objectives of this study were to find out whether or not videos plus discussion method was effective in improving the students’ listening and speaking achievements. This study involved one hundred and ninety six of the eighth grade students of SMP Negeri 6 Metro and forty of them were selected as the sample by using purposive sampling technique. The results of this study showed that the videos plus discussion method was considered as one of the effective ways to improve the students’ listening and speaking achievements.